1991
DOI: 10.1111/j.1440-1681.1991.tb01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Blood Pressure Control by Biofeedback: Relationship to Psychological Characteristics

Abstract: 1. Psychological characteristics were studied in 25 hypertensives (mean and standard deviation of blood pressure 150/95 +/- 12/5 mmHg), who received blood pressure (BP) biofeedback (BFB). Personality factors and success in BFB-BP modifying ability were correlated and the predictive value of psychological factors was estimated. 2. Questionnaires consisted of a Locus of Control of Behaviour (LCB) scale, the Spielberger state trait anxiety inventory and the Framingham Type A personality inventory. 3. BP was monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Furthermore, persons whose perceptions of control were more internal (that is, those who believed their behaviour was due more to their own efforts and ability) were generally those who were more able to reduce BP. These findings add weight to prior research in this area (Wittrock et al, 1988;Blanchard et al, 1989;Hunyor et al, 1991). This strengthens the belief that outcome and efficacy expectancies contribute to an individual's ability to control their BP.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Furthermore, persons whose perceptions of control were more internal (that is, those who believed their behaviour was due more to their own efforts and ability) were generally those who were more able to reduce BP. These findings add weight to prior research in this area (Wittrock et al, 1988;Blanchard et al, 1989;Hunyor et al, 1991). This strengthens the belief that outcome and efficacy expectancies contribute to an individual's ability to control their BP.…”
Section: Discussionsupporting
confidence: 79%
“…In a further study, McGrady and Higgins (1989) found lowering of BP was related to autonomic reactivity (such as high anxiety, higher cortisol levels and cool hands). Hunyor et al (1991) found associations between controlling BP and factors like expectancies (locus of control), and state and Blood Pressure Reduction 35 trait anxiety. McGrady (1994) showed that those who successfully reduced BP also reduced trait and state anxiety levels in comparison to controls.…”
Section: A R Craig Et Almentioning
confidence: 94%
See 1 more Smart Citation
“…Noninvasive continuous finger BP measurement has introduced a new method of BP feedback capability~Elbert et al, 1992;Hunyor et al, 1991;Sawada & Yamakoshi, 1991;Weitkunat et al, 1993! with advantages over intermittent feedback~Blanchard, Young, Haynes, & Kallman, 1974Gatchel, 1974;Pollard & Ashton, 1982!.…”
mentioning
confidence: 99%
“…Using continuous BP feedback, we found that 40% of both normotensive and hypertensive subjects could lower systolic blood pressure~SBP! by clinically relevant amounts of Ն5 mmHg in three studies~Cejnar, Hunyor, Liggins, & Bartrop, 1988;Hunyor et al, 1991Hunyor et al, , 1997! with reductions of 10 6 4.0, 15.3 6 7.5, and 11 6 5.6 mmHg, respectively, in the laboratory.…”
mentioning
confidence: 99%